PENGARUH SELF EFFICACY DAN PENGAMBILAN KEPUTUSAN TERHADAP KINERJA KEPALA MADRASAH TSANAWIYAH (MTS) SE-KABUPATEN TANAH DATAR - Helmizuldi Helmizuldi (IAIN Batusangkar, 2016)
his study was aimed at revealing the influence of self-efficacy and decision making on the headmasters’ job performance of Tsanawiyah Secondary School (MTs) In Tanah Datar. The sample of this study were the headmasters of Tsanawiyah Secondary School (MTs) in Tanah Datar consisted of 32 headmasters which were selected from 48 headmasters by using stratified proportional random sampling technique. The data were collected by using questionnaire. The findings revealed that (1) self efficacy significantly influenced 25,3% toward headmasters’ job performance; (2) decision making significantly influenced 27,4% toward headmasters’ job performance; and (3) self efficacy and decision making significantly influenced 38.8% toward headmasters’ job performance. It can be concluded that self efficacy and decision making were two important factors that influenced headmasters’ job performance of Tsanawiyah Secondary School (MTs) in Tanah Datar.Keywords: Self-Efficacy, Decision Making, Headmasters’ Job Performance, Tsanawiyah Secondary School